Cultural Diversity in Technology-Based Assessments: Innovations for Fair and Inclusive Evaluations in Higher Education - Kurniawan, Dwi Agus; Susbiyanto, Susbiyanto; Orongan, Marilyn; Cruz Olivares, Verónica; M. Mosalam, Esraa; Abbas Qanbar Al Saadi, Sahira (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study aims to explore the implementation of Technology-Based Assessment (TBA) with a multicultural approach in higher education to reduce cultural bias, increase accessibility, and create a fairer and more inclusive assessment system for students from various cultural backgrounds. Methodology: This study used a mixed-methods design with a convergent parallel approach. The sample in this study was taken using purposive sampling. Quantitative data were collected through an online survey using a Likert scale questionnaire created with Google Forms. Statistical analysis was performed using SPSS. Qualitative data were collected through semi-structured interviews. Thematic analysis was used to analyze qualitative data, ensuring comprehensive integration of findings. Main Findings: Multicultural Technology-Based Assessment (TBA) improves accessibility and flexibility of assessment in higher education. However, cultural biases in item design and language barriers have been found to impact perceptions of fairness and inclusivity. Students from different cultural backgrounds have varied experiences, highlighting the importance of adapting TBA to reflect cultural diversity. A multicultural approach to TBA has been shown to reduce disparities and support a more inclusive assessment environment. Novelty/Originality of this study: This study introduces a multicultural approach to Technology-Based Assessment (TBA) for the context of higher education in Indonesia, taking into account the diversity of cultures, languages, and local values. This study provides new insights into the development of inclusive and equitable TBA, offers practical solutions to reduce cultural bias, and broadens understanding in the design of technology-based assessments in multicultural environments.